The potential use of rabies virus glycoprotein-derived peptides to facilitate drug delivery into the central nervous system: a mini review. (28th May 2017) - Huey, Rachel; Hawthorne, Susan; McCarron, Paul
Abstract: Rabies virus glycoprotein (RVG), a 505 amino acid type-1 glycoprotein, is responsible for the neurotrophic nature of the rabies virus infection. Despite varying reports in the literature as to which receptor is ultimately responsible for interaction of RVG with the nervous system, there is a strong argument for major nicotinic acetylcholine receptor (nAChR) involvement. Peptide derivatives of RVG, such as rabies virus-derived peptide (RDP) and RVG-29 are emerging as promising targeting ligands for the delivery of therapeutics to the central nervous system (CNS). The neurotrophic nature of RVG and indeed its derivatives may be due to interaction with ubiquitous nAChRs principally, but also association with other neural cell-specific molecules such as neural cell adhesion molecule (NCAM). It is possible that nAChR-mediated uptake of RVG-derived peptides may serve as an attractive new approach for targeting drug delivery to the brain. Potential application of this type of drug delivery system extends to many diseases affecting the CNS, where specific and effective drug delivery is normally a challenging process.